2022
DOI: 10.3390/catal12101180
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Decorated 2D MXene (2D Ti3C2Tix) as a High-Performance Electrocatalyst for Reduction of Carbon Dioxide into Fuels toward Climate Change Mitigation

Abstract: Palladium nanoparticles (Pd NPs) have attracted considerable attention recently for their excellent catalytic properties in various catalysis reactions. However, Pd NPs have some drawbacks, including their high cost, susceptibility to deactivation, and the possibility of poisoning by intermediate products. Herein, Pd nanoparticles with an average diameter of 6.5 nm were successfully incorporated on electronically transparent 2D MXene (Ti3C2Tix) nanosheets (Pd-MXene) by microwave irradiation. Considering the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…34 In addition, bicarbonates as electrolyte is commonly used in electrocatalytic CO 2 RR. [23][24][25][26][27]35 The elucidation of pH, electrode potential, and electrolyte influence on the surface structure is paramount. In a thermodynamic context, the Pourbaix diagram serves as a powerful tool, delineating equilibrium surface structures across varying pH and applied potentials, thus facilitating the determination of active phases under diverse thermodynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 In addition, bicarbonates as electrolyte is commonly used in electrocatalytic CO 2 RR. [23][24][25][26][27]35 The elucidation of pH, electrode potential, and electrolyte influence on the surface structure is paramount. In a thermodynamic context, the Pourbaix diagram serves as a powerful tool, delineating equilibrium surface structures across varying pH and applied potentials, thus facilitating the determination of active phases under diverse thermodynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Strongin et al conducted electrocatalytic CO 2 RR on Mo 2 C and Ti 3 C 2 to make CO effectively . In recent reports, MXenes with various modifications had been exploited in electrocatalytic CO 2 RR with plausible performance. These pioneer studies about CO 2 RR on MXenes demonstrated the predicted promising capability of MXenes for CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pure Pd leads to a higher cost when considering its in commercial applications . Our previous studies demonstrate that the alloy formation of Ru–Pd is highly electroactive in the electrocatalysis application which make them in cost-effective Ru–Pd/WO 3 /MXene electrocatalyst for the adsorption and conversion of N 2 and CO 2 into urea. , Here, the fabrication of a Ru–Pd/WO 3 /MXene electrocatalyst was attempted to evaluate N 2 CO 2 RR in urea production. Electrocatalytic N 2 CO 2 RR uniquely requires hydrogen species at the cathode for effective urea conversion.…”
Section: Introductionmentioning
confidence: 99%
“…2 of 16 Ti 3 C 2 , the most common MXene, possesses a two-dimensional graphene-like structure, leading to its capabilities such as excellent light absorption, electrical conductivity and good hydrophilicity [42][43][44]. Thus, it has been used as a cocatalyst for photocatalysis reactions.…”
Section: Introductionmentioning
confidence: 99%